Dziennik [Diary] by Władysław Konopczyński on Writing a Biography of Stanisław Konarski - Piotr Biliński; Zofia Zielińska (Acta Universitatis Carolinae: Historia Universitatis Carolinae Pragensis, 2022)
Stanisław Konarski (1700–1773) – a Piarist, playwright, poet, translator, publisher, publicist, reformer of education, and founder of the Collegium Nobilium; one of the most important personages of eighteenth-century Polish history. His earliest scientific biography was written by the Krakow historian Władysław Konopczyński in 1926. Based on Konopczyński’s Diary¸ this study presents a reconstruction of work on this important book and challenges surrounding its publication.